Genetic Connectivity of the West Indian Manatee in the Southern Range and Limited Evidence of Hybridization With Amazonian Manatees - Luna, Fábia de Oliveira; Beaver, Caitlin E.; Nourisson, Coralie; Bonde, Robert K.; Attademo, Fernanda L. N.; Miranda, Adriana Vieira; Torres-Florez, Juan Pablo; de Sousa, Glaucia Pereira; Passavante, José Zanon; Hunter, Margaret E. (Frontiers in Marine Science, 2021)
The Antillean subspecies of the West Indian manatee is classified as endangered by the International Union for the Conservation of Nature (IUCN) Red List. In Brazil, the manatee population is listed as endangered with an estimated population size of 500 - 1‚000. Historic hunting, recent habitat degradation, and fisheries bycatch have decreased the population size. The Amazonian manatee is listed as vulnerable by the IUCN with unknown population sizes within Brazil. The Antillean manatee occurs in sympatry with the Amazonian manatee in Brazil and hybridization has been previously indicated. To provide information on the genetic structure, diversity, and degree of hybridization in the sympatric zone near the Amazon River mouth, the mitochondrial DNA control region and 13 nuclear microsatellite markers were assessed on the two species. Samples were analyzed from the Antillean subspecies across its distribution in Brazil (n=78) and from the Amazonian species (n=17) at the Amazon river mouth and inland mainstem river. To assess the previously defined evolutionary significant units of Antillean manatees in the area, an additional 11 samples from Venezuela and Guyana were included. The Antillean manatee was found to be a single population in Brazil and had lower than average number of alleles (3.00), expected heterozygosity (0.34), and haplotype diversity (0.15) when compared to many other manatee populations. The low values may be influenced by the small population size and extended pressures from anthropogenic threats. Gene flow was identified with Venezuela/Guyana in admixed Antillean Brazil samples, although the two populations were found to be moderately divergent. The nuclear loci in Venezuela/Guyana Antillean manatee samples indicated high differentiation from the samples collected in the Amazon River (FST=0.35 and RST=0.18, p=0.0001). No indication of nuclear hybridization was found except for a single sample, ‘Poque’ that had been identified previously. The distribution of Antillean manatees in Brazil is extensive and the areas with unique habitat and threats would benefit from independent management and conservation actions. Gene flow, genetic diversity, and long-term population stability could be improved through habitat restoration, protected area -- particularly for parturition and neonatal calves, and the designation of travel corridors throughout the southern range.